2018
DOI: 10.1021/acsami.7b19640
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of Cisplatin(IV) Prodrug-Tethered CuFeS2 Nanoparticles in Tumor-Targeted Chemotherapy and Photothermal Therapy

Abstract: In this study, for the first time, CuFeS nanocrystals were successfully prepared through a facile noninjection-based synthetic strategy, by reacting Cu and Fe precursors with dodecanethiol in a 1-octadecene solvent. This one-pot noninjection strategy features easy handling, large-scale production, and high synthetic reproducibility. Following hyaluronic acid (HA) encapsulation, CuFeS nanocrystals coated with HA (CuFeS@HA) not only readily dispersed in water and showed improved biocompatibility but also possess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 64 publications
2
29
0
Order By: Relevance
“…PTT uses photon energy to heat tumors physically, but PDT utilizes photosensitizers (PSs) to generate cytotoxic reactive oxygen species (ROS) and induce cancer cell death [111]. Phototherapies exhibit several advantages over traditional radiotherapy and chemotherapy, including their noninvasive nature, high selectivity, and a low number of side effects [112,113]. However, single phototherapy cannot completely eradicate a tumor because the laser intensity inevitably decays with the depth of the biological tissue, and the uneven distribution of the heat generated in the tissue damages normal tissues [114,115].…”
Section: Photo-chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…PTT uses photon energy to heat tumors physically, but PDT utilizes photosensitizers (PSs) to generate cytotoxic reactive oxygen species (ROS) and induce cancer cell death [111]. Phototherapies exhibit several advantages over traditional radiotherapy and chemotherapy, including their noninvasive nature, high selectivity, and a low number of side effects [112,113]. However, single phototherapy cannot completely eradicate a tumor because the laser intensity inevitably decays with the depth of the biological tissue, and the uneven distribution of the heat generated in the tissue damages normal tissues [114,115].…”
Section: Photo-chemotherapymentioning
confidence: 99%
“…PTT uses photon energy to heat tumors physically, but PDT utilizes photosensitizers (PSs) to generate cytotoxic reactive oxygen species (ROS) and induce cancer cell death [111]. Phototherapies exhibit several advantages over traditional radiotherapy and chemotherapy, including their noninvasive nature, high selectivity, and a low number of side effects [112,113]. However, single…”
Section: Photo-chemotherapymentioning
confidence: 99%
“…CuFeS 2 ‐CS‐Pt with irradiation achieved remarkable anticancer effects in mice bearing A549 tumor, and the tumor was eliminated completely in two of four mice. Chang et al coated CuFeS 2 with HA and loaded DSCP to yield CuFeS 2 @HA‐Pt(IV) for combinatorial therapy 68 . The hybrid displayed a superior high photothermal conversion efficacy of 74.2% and significantly inhibited B16F1 cancer cell proliferation.…”
Section: Combination Of Platinum Chemotherapy With Pttmentioning
confidence: 99%
“…CIS QDs bonded with doxorubicin (DOX), an anti-cancer drug was reported to effectively deliver DOX to the targeted cancer cells [59]. In another study, Girma et al [126] described the conjugation of synthesised CuFeS 2 NPs with anti-cancer drug cisplatin (IV). The study revealed that the CuFeS 2 NPs drug conjugate reduced the side effect of the drug on normal tissues.…”
Section: Drug Deliverymentioning
confidence: 99%